2019
DOI: 10.1021/acs.iecr.9b00634
|View full text |Cite
|
Sign up to set email alerts
|

Production of Oil-in-Water Emulsions with Varying Dispersed-Phase Content using Confined Impinging Jet Mixers

Abstract: This work reports for the first time on the use of Confined Impinging Jet Mixers (CIJM) for the production of emulsions with dispersed-phase content up to 80 wt %, in both the surfactant-poor and -rich regimes, following the exposure to varying CIJM hydrodynamic conditions. It was observed computationally and experimentally that the CIJM capacity resulted strictly dependent on the mass jet flow rate (W jet > 176 g/min) and the pre-emulsion droplet size (>10 μm). CIJM emulsification performance remained (almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…It should be highlighted that, as previously discussed, the pre-emulsions containing 0.10 wt.% silica phase separated immediately after their preparation, whereas, in our previous work, we showed that although the emulsions stabilised by only 0.01 wt.% Tween20 remained stable after CIJs processing (d3,2 ~ 25µm), these phase separated during the storage period, i.e. 40 days (Tripodi et al, 2019). Thus, there is a clear evidence that the combination of the emulsifiers (even at concentrations where each of them on their own do not give a stable emulsion microstructure) aids in prolonging the emulsion stability, although in this case the droplet size was not entirely retained (Figure 7.B).…”
Section: Long-term Emulsion Stabilitysupporting
confidence: 49%
See 4 more Smart Citations
“…It should be highlighted that, as previously discussed, the pre-emulsions containing 0.10 wt.% silica phase separated immediately after their preparation, whereas, in our previous work, we showed that although the emulsions stabilised by only 0.01 wt.% Tween20 remained stable after CIJs processing (d3,2 ~ 25µm), these phase separated during the storage period, i.e. 40 days (Tripodi et al, 2019). Thus, there is a clear evidence that the combination of the emulsifiers (even at concentrations where each of them on their own do not give a stable emulsion microstructure) aids in prolonging the emulsion stability, although in this case the droplet size was not entirely retained (Figure 7.B).…”
Section: Long-term Emulsion Stabilitysupporting
confidence: 49%
“…On the other hand, as the ε̅ th increased (highlighted areas in Figure 3), the droplet size reduction became more pronounced and all systems reached the lowest droplet size (~10 µm) at the highest value of ε̅ th regardless of particle concentration and oil content. In a recently published study (Tripodi et al, 2019), it was demonstrated that the jet collision was compromised at low ε̅ th , resulting in relatively poor mixing conditions and ultimately impeding CIJs emulsification capacity (within this energy dissipation rate range) . Contrarily, as higher levels of ε̅ th are approached (i.e.…”
Section: O/w Emulsions Solely Stabilised By Particlesmentioning
confidence: 99%
See 3 more Smart Citations